Sistem Informasi Peminjaman Laboratorium pada Cross-Platform dengan Metode Prototyping (Studi Kasus: Politeknik Caltex Riau) - Leony Veronica Wijaya; Shumaya Resty Ramadhani (Politeknik Negeri Batam, 2020)
The Laboratory information system is one of the information systems that was built by the BSTI of Polytechnic Caltex Riau to provide information about laboratory lending. This system is also being intended to the person who is in charge of approving laboratory lending such as the head of the laboratory, and laboratory assistant in case of monitoring some of the laboratories that are lent. However, the features provided by this information system are not enough to support the process of laboratory lending. Therefore, a mobile application with the quality of Cross-Platform was built, in other words, it can be used on iOS and Android platforms. One of the technologies that can be used to build a cross-platform application is the React Native. This application was built with a prototype method that is used to get more perspective points from users with interviews and can simplify the development of this application to be effective. This application was developed with Laravel, Firebase Authentication, and MySQL. Because there are several problems with the old system, an application that offers several solutions consists of avasisten instruktur laboratoriumbility in the lending laboratory, receiving legal paper of laboratory lending, and receiving notification were developed in this study. The main feature provided in this application is the evidence letter of laboratory lending that doesn’t have to be printed so that can reduce paper usage. As a result, 94.1% of respondents stated that this application’s features can run well and make it easy for college students to propose laboratory lending.